2021
DOI: 10.1371/journal.pone.0251863
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise training on heart rate variability in type 2 diabetes mellitus patients: A systematic review and meta-analysis

Abstract: Background Cardiac autonomic neuropathy is a common complication of type 2 diabetes mellitus (T2DM), that can be measured through heart rate variability (HRV)–known to be decreased in T2DM. Physical exercise can improve HRV in healthy population, however results are under debate in T2DM. We conducted a systemic review and meta-analysis to assess the effects of physical exercise on HRV in T2DM patients. Method PubMed, Cochrane, Embase, and ScienceDirect databases were searched for all studies reporting HRV pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 87 publications
(459 reference statements)
4
31
0
Order By: Relevance
“…Several studies have indicated a positive relationship between controlled metabolic parameters, cardiovascular fitness, and autonomic modulation of HRV. [103][104][105][106] Among these effects, the improvement in glucose metabolism associated with an increase in insulin sensitivity stands out. Other important effects have also been observed, such as reduction in fat mass, improvement in body composition, and reduction in inflammatory and oxidative stress markers.…”
Section: Metabolic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated a positive relationship between controlled metabolic parameters, cardiovascular fitness, and autonomic modulation of HRV. [103][104][105][106] Among these effects, the improvement in glucose metabolism associated with an increase in insulin sensitivity stands out. Other important effects have also been observed, such as reduction in fat mass, improvement in body composition, and reduction in inflammatory and oxidative stress markers.…”
Section: Metabolic Diseasesmentioning
confidence: 99%
“…104,105,[107][108][109][110] Consequently, all these beneficial effects resulting from the increase in cardiovascular fitness can contribute to the improvement on autonomic modulation of HRV. That is, increased cardiovascular fitness results in a better balance of cardiac autonomic modulation, characterized by increased vagal modulation and/or reduced sympathetic modulation, 106,109,111 which has been observed in patients with major complications and comorbidities due to diabetes. 112,113 Furthermore, all these benefits of better cardiovascular fitness, in addition to contributing to the regulation of the autonomic modulation of HRV, also contribute to the prevention of cardiovascular diseases and improvement in quality of life in general.…”
Section: Metabolic Diseasesmentioning
confidence: 99%
“…Heart rate in any state of rest, deep breathing, recovery, and lying to standing are highest in known diabetic conditions. Resting heart rate can be a crucial factor in the early detection of COVID-19, whereas extreme elevation of an individual's resting heart rate can be an early sign that he or she is infected with COVID-19, or simply requires medical attention [28]. The results in this study were compared to those reported in [13] and for commercialised pulse oximeters, showing a more or less similar accuracy of 97%.…”
Section: -1-heart Rate Resultsmentioning
confidence: 58%
“…In fact, some CVD risk models derived for the general population have been shown to be suboptimal when applied to patients with T2D [ 5 , 6 ]. In patients with type 2 diabetes (T2D), different exercise modalities, such as walking, aerobic, resistance, strength, yoga or certain combinations, have been found to improve the levels of the most important CVD risk factors, including hemoglobin A1c (HbA1c), glucose, low-density lipoprotein (LDL), total cholesterol, heart rate and weight [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Most of the evidence relating to PA and CVD risk is based on short-term interventional randomized clinical trials and focused on these intermediate outcomes.…”
Section: Introductionmentioning
confidence: 99%